PEMBERDAYAAN MASYARAKAT DESA BOROK TOYANG DALAM MENGOLAH SAMPAH MENJADI PRODUK KREATIF - Wicarya, I Putu Ngurah Dharma; Safitri, Anggraini; Rahmatika, Ainur; Yunitasari, Ria; Trisaputri, Kurnia; Meliyasa, Nuzhatul Pramudya; Mutahharun, Tanzil; Aji, Muhamad Asrul; Ilham, Dzira Al Zena; Tiarany, Qoria Fista (Universitas Mataram, 2024)
Borok Toyang Village is one of the villages located in West Sakra Subdistrict, East Lombok Regency, West Nusa Tenggara Province, Indonesia. The village consists of eight hamlets, namely Borok Duah Hamlet, Borok Dalem Hamlet, Kondok Hamlet, Montong Kesik Hamlet, Tenges Enges Hamlet, Toyang Hamlet, Dewe Lanji Hamlet, and Peresak Hamlet. Of the eight hamlets, Toyang and Borok are the largest. The residents of Borok Toyang are predominantly farmers, with around 80% of them working in agriculture. They usually grow rice in the rainy season and tobacco in the dry season. However, due to difficulties in growing tobacco, some farmers have switched to growing vegetables such as chilies and tomatoes. In addition to farming, about 25% of the residents also manage private farms, mainly goats. Despite the great potential in agriculture and animal husbandry, the Borok Toyang community faces several challenges, such as suboptimal manure management and conventional waste disposal without adequate treatment. The results of this empowerment contain the awareness of the community about the current condition of waste, conducting a Zero Waste lifestyle movement to minimize waste by providing them with waste facilities, and sorting waste to be utilized which can later help the community a little to make crafts from the waste.